2009
DOI: 10.1080/09518390903333889
|View full text |Cite
|
Sign up to set email alerts
|

Niggers no more: a critical race counternarrative on Black male student achievement at predominantly White colleges and universities

Abstract: A methodological approach popularized by critical race theorists is used in this article to oppose dominant discourse concerning the social and educational status of Black men in America. Specifically, this counternarrative on student achievement was derived from face-to-face individual interviews with 143 Black male undergraduates at 30 predominantly White colleges and universities across the USA. Exemplified via five composites constructed from the overall sample are resistant responses to subordination and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
249
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 262 publications
(254 citation statements)
references
References 30 publications
(26 reference statements)
4
249
0
1
Order By: Relevance
“…Anti-deficit inquiry also recognizes students of color as experts on their experiential realities, and empowers them to offer counternarratives concerning their academic success (Harper, 2009;Solórzano and Yosso, 2002;Yosso, 2005 (Stanley, 2007). This study aims to answer remaining questions as to how, despite adversity, some adult African American women obtained their bachelor degrees.…”
Section: Anti-deficit Inquirymentioning
confidence: 99%
See 2 more Smart Citations
“…Anti-deficit inquiry also recognizes students of color as experts on their experiential realities, and empowers them to offer counternarratives concerning their academic success (Harper, 2009;Solórzano and Yosso, 2002;Yosso, 2005 (Stanley, 2007). This study aims to answer remaining questions as to how, despite adversity, some adult African American women obtained their bachelor degrees.…”
Section: Anti-deficit Inquirymentioning
confidence: 99%
“…Majoritarian stories are also stories of other forms of privilege such as gender and class. Harper (2009) points out that the goal of counternarratives is not to focus on convincing the White mainstream that racism exists but to reflect on the lived experiences of racially and socially marginalized people of color. It is a means of stretching the boundaries of the White mainstream to give voice, perspective and consciousness to those previously suppressed, devalued and abnormalized (Delgado, 1999).…”
Section: Counternarrativesmentioning
confidence: 99%
See 1 more Smart Citation
“…Cuyjet (2006b) concurred that this also holds true for Black college students. In studies of Black males attending predominantly White institutions, Harper (2004;2009b) found that Black male students engaged in formal social and academic activities that extended beyond the classroom were more likely to develop a positive racial identity, and thus persist to graduation. Based on his findings, Harper (2009b, p. 700) contended that it is critical that Black male college students become "actively engaged in purposeful activities both inside and outside the classroom."…”
Section: Astin's Theory Of Involvementmentioning
confidence: 99%
“…They reported their commitment to succeeding inspires other African Americans to realize their goals. Harper (2009b) contended that it is critical that Black male college students become actively engaged in "educationally purposeful activities, both inside and outside the classroom" (p. 700). This is consistent with Tinto's and Astin's arguments favoring service-learning (or course-based) activities that foster social and academic integration through directed action.…”
Section: Department Of Education 2012) the Difficulties Are Implicimentioning
confidence: 99%